Physical Health and Cognitive Outcomes in Elderly School Members: Insights from a Cross-Sectional Study. - PAKULANON, Sasima; PETVISET, Haruthai; YINGYONGSAKSRI, Supannikar (Turkiye Klinikleri Journal of Medical Sciences, 2026)
Objective: This descriptive cross-sectional study aimed to investigate the characteristics of physical fitness, physical activity, depression, and cognitive function among members of elderly schools. Material and Methods: 216 participants provided information on their health status, including age, sex, and educational level. Thai Geriatric Depression Scale-15 was employed to assess depression. The Montreal Cognitive Assessment Thai (MoCA-T) version was used to assess cognitive impairment. Height and body mass were measured using standard anthropometric techniques, and body mass index (BMI) was calculated. The Senior Fitness Test was utilized to assess physical fitness. Results: Most participants demonstrated normal BMI, had low levels of formal education, and exhibited high rates of hypertension, while smoking and alcohol use were uncommon. Despite reporting high levels of physical activity and performing within the normal range on fitness tests, 83.3% showed delayed times on the 8-foot Up-and-Go test. MoCA-T results indicated that most participants had mild to moderate cognitive impairment (44.4% and 42.6%, respectively), and 91.7% reported no depressive symptoms. Conclusion: This study highlights a paradox between high physical activity and a high prevalence of cognitive impairment, suggesting that education and chronic health conditions may play a role in cognitive outcomes. However, the use of a convenience sample, descriptive design, and lack of inferential analysis limit generalizability and causal interpretation. Future research should use representative samples, longitudinal designs, and multi-site to clarify causal pathways and enhance the generalizability of findings to diverse older adult populations.